2007
DOI: 10.1007/s00540-006-0457-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of fentanyl and remifentanil on splanchnic tissue perfusion during cardiac surgery

Abstract: The purpose of this study was to compare the effects of fentanyl and remifentanil on splanchnic perfusion during coronary artery bypass graft (CABG) surgery. Fifty patients were randomized to receive either fentanyl (10 microgxkg(-1) at induction and 5 microgxkg(-1)xh(-1) infusion for maintenance) or remifentanil (3 microgxkg(-1) at induction and 1 microgxkg(-1)xmin(-1) infusion for maintenance). Patients in both groups were comparable with regard to demographics. Intraoperative volume management and inotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Furthermore, fentanyl has been commonly used for patients undergoing cardiac operations because high doses of fentanyl can stabilize the cardiovascular circulatory system during operations. After administration of 50-100 μg/kg fentanyl, the plasma concentration of fentanyl in these patients is commonly above 20-30 ng/mL [9] . However, high plasma concentrations of fentanyl are associated with clinical side effects such as nausea and vomiting, constipation, skin itching and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fentanyl has been commonly used for patients undergoing cardiac operations because high doses of fentanyl can stabilize the cardiovascular circulatory system during operations. After administration of 50-100 μg/kg fentanyl, the plasma concentration of fentanyl in these patients is commonly above 20-30 ng/mL [9] . However, high plasma concentrations of fentanyl are associated with clinical side effects such as nausea and vomiting, constipation, skin itching and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…Безпосередній вплив опіоїдів на спланхнічний кровоплин вивчений недостатньо. За даними Bedirli та ін., у пацієнтів, яким проводилось аортокоронарне шунтування, застосування опіоїдів призводило до погіршення показників спланхнічного кровоплину (pH та P CO 2 слизової шлунку) оціненого методом шлункової тонометрії, що автори частково пов'язували з депресією системної гемодинаміки [17]. За результатами нашого дослідження у дітей без ІАГ, з ІАГ та з АКС, що знеболювались пролонгованою інфузією морфіну спостерігались статистично значуще нижчі показники BFI SMA у порівнянні із групами «Лідокаїн» та «ЕДА» та статистично значуще нижчі показники BFI PV у дітей з ІАГ та з АКС у порівнянні з групою «ЕДА».…”
Section: вступunclassified
“…Remifentanil has gained increased attention due to its possible fast-track potential with shorter ventilation time, shorter admission in the ICU [6,7] and improved postoperative quality [8]. However, some studies have shown less haemodynamic stability after remifentanil compared to other opioids [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%